FINANCIAL RISKS IN PLANNING AND OPTIMIZING GOVERNMENT EXPENDITURES (Ustozlar uchun, 2024)
Annotatsiya: Financial risks in planning and optimizing government expenditures pose significant challenges to fiscal sustainability and effective governance, requiring comprehensive risk management strategies to mitigate potential negative impacts on public finances and economic stability.